Representasi Kesantunan Berbahasa Jepang: Analisis Keigo Tokoh Togo Nitta dalam Ousama Ni Sasagu Kusuriyubi - I Gusti Ayu Regina Dhiras; Ni Luh Gede Meilantari (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
This study examines the use of keigo (honorific speech) by the character Togo Nitta in the Japanese drama Ousama ni Sasagu Kusuriyubi. The research focuses on identifying the forms of keigo employed by the main character in his communicative interactions. The method applied is the observational note-taking technique, which involves carefully watching the drama, transcribing all utterances containing keigo and subsequently conducting a qualitative analysis. The data analyses employ Tsujimura’s (1991) framework of keigo, which classifies honorific expressions into three primary categories. These categories are sonkeigo (respectful language), kenjogo (humble language) and teineigo (polite language). The finding indicates that teineigo dominates Togo Nitta’s use of keigo. This form is consistently utilized to refine conversation and express politeness between the speaker and interlocutor, irrespective of relative social status. Specifically, the study identifies four lexemes realized in teineigo form and three lexemes in kenjogo form. The use of kenjogo generally occurs in contexts where Togo Nitta needs to humble himself or his in group (uchi) towards an interlocutor of higher status. These findings suggest that the character’s politeness and adapting to social norms across various situasions, as represented within the drama’s narrative.